ERRORS MADE IN GOOGLE TRANSLATE IN THE INDONESIAN TO ENGLISH TRANSLATIONS OF NEWS ITEM TEXTS - Ismail, Adam; Hartono, Rudi (ELT Forum: Journal of English Language Teaching, 2016)
The objective of this study was to describe the errors made in the Indonesian to English Google Translate translations of News Item texts. This study employed five English translations of Indonesian News Item texts taken from (1) bbc.com, (2) kompas.com, (3) liputan6.com, (4) tempo.co, and (5) viva.co.id made by using Google Translate. Those samples were taken by using purposive sampling technique. The categorization of translation errors were adapted from Dewiâs Indonesian-English translation error typology. The errors can occur in the words, phrases, clauses, and sentences of the texts. The data gathered were analyzed descriptively by using qualitative approach. The findings of the analysis showed that there were 13 categories of translation errors obtained from 278 data. Ranking from the most common to the least common errors found in the data, they were grammatical errors (24.46%), terminology errors (15.47%), omission errors (14.03%), syntax errors (12.23%), mistranslation/misunderstanding errors (6.47%), literalness/faithfulness errors (6.47%), usage errors (6.12%), punctuation errors (3.60%), addition errors (2.88%), ambiguity errors (2.52%), word form errors (2.52%), capitalization errors (2.16%), and spelling errors (1.08%). The data findings also showed that statistical method of Google Translate, the inability of Google Translate to understand the contexts of the texts beyond sentence, and errors in the source texts that carried into translation errors in the target texts were the causes of translation errors found in the data.